Variability in Retinal Neuron Populations and Associated Variations in Mass Transport Systems of the Retina in Health and Aging - Zouache, Moussa A. (Frontiers in Aging Neuroscience, 2022)
Aging is associated with a broad range of visual impairments that can have dramatic consequences on the quality of life of those impacted. These changes are driven by a complex series of alterations affecting interactions between multiple cellular and extracellular elements. The resilience of many of these interactions may be key to minimal loss of visual function in aging; yet many of them remain poorly understood. In this review, we focus on the relation between retinal neurons and their respective mass transport systems. These metabolite delivery systems include the retinal vasculature, which lies within the inner portion of the retina, and the choroidal vasculature located externally to the retinal tissue. A framework for investigation is proposed and applied to identify the structures and processes determining retinal mass transport at the cellular and tissue levels. Spatial variability in the structure of the retina and changes observed in aging are then harnessed to explore the relation between variations in neuron populations and those seen among retinal metabolite delivery systems. Existing data demonstrate that the relation between inner retinal neurons and their mass transport systems is different in nature from that observed between the outer retina and choroid. The most prominent structural changes observed across the eye and in aging are seen in Bruch’s membrane, which forms a selective barrier to mass transfers at the interface between the choroidal vasculature and the outer retina.